The Hellenistic gymnasium and the pleasure of “paideia” - Troncoso, Victor Alonso (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The author tries to investigate the function of the gymnasium, undoubtedly a fundamental institution of the Hellenistic world (336-30 B.C.). In Hellenistic times it played a very important role also as educational centre and as an instrument of socializing and integration in the cultural life. The “men of the gymnasium” represented the leading social groups in the old and new polis of the Hellenistic oikoumene. In this context it would not be strange to find the emergence of a new concept of the paideia as a specially pleasant activity.
Keywords: Gymnasium; Education; Paideia